The long course of environmental action in schools. A case study in Aragón - Marcén Albero, Carmelo (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
Making the curriculum environmentally friendly in schools is a complex task. Although it rests on the increasing interest for environmental questions, it fits into the present methodology in a difficult way, due to its great concern for contents. Even so, it is possible because there is a certain professional practice to work on certain environmental questions. Programming investigations to know the features of the present eco-friendly actions is a good way to build projects from them with new dimensions. These investigations need to know the key contents in the environmental dynamics, to design the contexts of intervention and to coordinate the processes that should be carried out to achieve a true green action in schools. That is the path that was followed in the investigation presented here.